(untitled) (Contemporary Journal of Social Science Review, 2025)
Bahawalpur’s stamps have a rich and varied history, seeing much evolution, first during the British Raj, then in the brief period that it existed as an independent state, and finally after it became a part of Pakistan. This study is confined to the same period. The aim is to evaluate on the basis of recent evidence how the stamps of Bahawalpur served purposes pertinent to those of the Raj and the Amir, and how the issuance of new stamps is interlocked with other historical developments. Aside from this, certain characteristics of the stamps will also be examined and an inferential account will be drawn.